A Geopolitical and Geo-economic Overview: On the Rise of China and India as Two Asian Giants - Schurer, Wolfgang (Tufts Archival Research Center, 2005)
Volume 29, Issue 2. Summer In his detailed account of the forces driving these two dynamos, Wolfgang Schurer explores the effect China and India will have on the rest of the world in the coming century.